Why do patients in pre-anti retroviral therapy (ART) care default: A cross-sectional study - Jaya Chakravarty; Sangeeta Kansal; Narendra Tiwary; Shyam Sundar (Wolters Kluwer Medknow Publications, 2016)
Background and Objectives: Approximately, 40% of the patients registered in the National AIDS Control Program in India are not on antiretroviral therapy (ART), i.e., are in pre-ART care. However, there are scarce data regarding the retention of pre-ART patients under routine program conditions. The main objective of this study was to find out the reasons for default among patients in pre-ART care. Materials and Methods: Patients enrolled in the ART Centre, Banaras Hindu University (BHU) between January and December 2009 and in pre-ART care were included in the study. Defaulters were those pre-ART patients who missed their last appointment of CD4 count by more than 1 month. Defaulters were traced telephonically in 2011 and those who returned and gave their consent for the study were interviewed using a semi-structured questionnaire. Results: Out of 620 patients in pre-ART care, 384 (68.2%) were defaulters. One hundred forty-four of the defaulters were traced and only 83 reached the ART center for interview. Among defaulters who did not reach the ART center, illiterate and unmarried were significantly more and mean duration from registration to default was also significantly less as compared to those who came back for the interview. Most defaulters gave more than one reason for defaulting that were as follows: Inconvenient clinic timings (98%), need for multiple mode of transport (92%), perceived improved health (65%), distance of center from home (61%), lack of social support (62%), and financial difficulty (59%). Interpretation and Conclusion: Active tracing of pre-ART patients through outreach and strengthening of the Link ART centers will improve the retention of patients in the program.